PREVALENSI STATUS GIZI PADA BALITA DAN FAKTOR YANG MEMPENGARUHINYA - Lestari, Sri; Sugiharto, Septiono Bangun; Heriyawan, Taufik (Jurnal Bina Cipta Husada, 2024)
The condition of malnutrition in children under five years will have an impact on the future of children and the quality of the next generation of the nation. This situation can be categorized with nutritional status, less, and more. This study aims to examine the correlation of factors that influence children nutrion  in the working area of Puskesmas Kalimanah, Purbalingga in 2021. This study uses an analytical survey design with a cross sectional approach. The sample in this study was 83 childrens aged 12-59 months. The sampling technique used is Simple Random Sampling. The measuring instrument used is a questionnaire sheet, children scales and children nutritional qualification sheets according to WHO NHCS. Data analysis consisted of univariate analysis and bivariat using Chi Square statistics and contingency coefficients. There were p-value=0.648 for education and C=0.469 for nutritional knowledge, in parenting and posyandu visits obtained p-value=0.001 with a value of C=0.387, on p-value income=0.0006 with value C=0.309, and for the history of infectious disease obtained p-value=0.010 with a value of C=0.317. For all variables obtained P-Value<0.05. There is a correlation between all variabels with children nutritional status. Which has a very strong stool is education.